The Influence of Prosocial Behavior and Parental Support on Students' Interest in Studying at Parbuluan 1 Public High School in Dairi Regency - Marulitua Pasaribu, Marhehe Sahala (Lembaga Riset Mutiara Akbar, 2022)
This study aims to determine the significant effect of Prosocial Behavior and Parental Support on Students' Interest in Learning at SMA Negeri 1 Parbuluan, Dairi Regency. The research method is a quantitative descriptive correlational type by placing the research variables in two groups, namely the independent variable and the dependent variable. The research population is SMA Negeri 1 Parbuluan, Dairi Regency. The sampling technique used was purposive sampling with a selected sample size of 100 children, the data collection method used prosocial behavior questionnaires, parental support questionnaires, and student learning interest questionnaires. The analysis used is Multiple Regression Analysis. Analysis of research data shows that (1) there is a significant effect of prosocial behavior on students' interest in learning which is indicated by the coefficient R = 0.561 and p = 0.000, namely p < 0.00; (2) there is a significant effect of parental support on student interest in learning, which is indicated by the coefficient R = 0.138 and p = 0.000, namely p <0.05 and (3) a significant effect of prosocial behavior and parental support on student interest in learning. indicated by the coefficient F = 25.996 and R (regression coefficient) = 0.591 while R2 = 0.349 with p < 0.05 and Std. Error of the Estimate 9.46953, The accuracy rate is 100% - 9.46953= 90.53047%. The third hypothesis in this study is to determine the effect of prosocial behavior and parental support on students' interest in learning.